Bangladesh Development Update, April 2018 : Building on Resilience - World Bank (World Bank, Dhaka, 2018)
Industrial production and services growth remained resilient. Inflation has accelerated, primarily due to supply shocks. Monetary policy has been accommodative. Financial sector vulnerability is rising. With a tightening of prudential controls, lending rates are back to double digits. Despite significant recovery in both exports and remittances, the current account deficit widened sharply, driven by a surge in imports. The overall balance of payments swung into deficit for the first time since FY11. Consequently, the exchange rate has depreciated. Interventions to smoothen exchange rate adjustments have eroded foreign exchange reserves. The fiscal deficit has been contained as weak revenue growth was counterbalanced by even weaker growth in expenditures. GDP growth is projected in the 6.5-7 percent range in the medium-term, while macro stability will require heightened vigilance. Poverty reduction has continued but slowed. The amount of poverty reduction achieved by each percent of growth fell by a third. Extreme poverty is projected to fall modestly to 11-12 percent in the medium-term. Downside risks center on the solvency of banks and the run-up to elections elevating instability and policy uncertainty. Going forward, investment and innovation enabling reforms will be key to accelerating development progress.